2008
DOI: 10.1128/jb.00194-08
|View full text |Cite
|
Sign up to set email alerts
|

NagA-Dependent Uptake ofN-Acetyl-Glucosamine andN-Acetyl-Chitin Oligosaccharides across the Outer Membrane ofCaulobacter crescentus

Abstract: Among the 67 predicted TonB-dependent outer membrane transporters of Caulobacter crescentus, NagA was found to be essential for growth on N-acetyl-␤-D-glucosamine (GlcNAc) and larger chitin oligosaccharides. NagA (93 kDa) has a predicted typical domain structure of an outer membrane transport protein: a signal sequence, the TonB box EQVVIT, a hatch domain of 147 residues, and a ␤-barrel composed of 22 antiparallel ␤-strands linked by large surface loops and very short periplasmic turns. Mutations in tonB1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 57 publications
1
49
1
1
Order By: Relevance
“…Thus, TolA and TolB are essential for viability. It was reported previously that genes encoding two other components of the Caulobacter Tol-Pal complex, tolQ and tolR, are essential (17).…”
Section: Vol 192 2010mentioning
confidence: 99%
“…Thus, TolA and TolB are essential for viability. It was reported previously that genes encoding two other components of the Caulobacter Tol-Pal complex, tolQ and tolR, are essential (17).…”
Section: Vol 192 2010mentioning
confidence: 99%
“…Later, some TBDRs were shown to be responsible for the import of non-Fe compounds (44), such as vitamin B12 (20), sugars (4,11,30), and non-Fe cations (43,52). Compared to porins, which allow the passive transport of molecules, TBDRs exhibit high affinity to their ligands: the Kd of SuxA for sucrose is 330 nM (4) while that of FepA for ferric enterobactin is 24 nM (35).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of the C. crescentus genome revealed that this bacterium possesses an unusually large number of TonB-dependent receptors, outer membrane proteins that bind to diverse substrates and facilitate their transport across the outer membrane and ultimately into the cytoplasm (28). It has been hypothesized that this diverse group of TonB-dependent receptors enables C. crescentus to diversify its nutrient uptake mechanisms during periods of nutrient deprivation, and two of these TonB-dependent receptors have been implicated in the uptake of the carbon sources maltodextrin (17) and N-acetylglucosamine (5). In addition to TonB-dependent receptors, C. crescentus also employs the intracellular second messenger ppGpp to adapt to carbon starvation (16).…”
mentioning
confidence: 99%